Building façade integrated solar thermal collectors for air heating: experimentation, modelling and applications - Agathokleous, Rafaela; Barone, Giovanni; Buonomano, Annamaria; Forzano, Cesare; Kalogirou, Soteris A.; Palombo, Adolfo (My University, 2019)
In this paper the design and the energy performance investigation of a new flat-plate solar thermal air collector prototype is presented. The adoption of cost-effective materials and simple design solutions represent the main novelties of the proposed device when compared to existing commercial collectors. In addition, the prototype is suitably designed to be integrated into the building envelope (façade), which is a key feature for the market uptake of building integrated solar thermal systems. The paper includes the description of the dynamic simulation model, developed for the energy and economic performance analyses of the whole building-prototype system. The simulation model, implemented with a computer code written in MatLab, is able to predict both active (hot air production for building space heating) and passive (winter free heating and summer overheating) effects due to the building integration of the proposed solar collector. By such tool, indoor comfort investigations can also be carried out. The dynamic simulation models of both the building and the collector prototype were successfully validated. In order to show the features of the developed simulation code, a suitable case study was carried out. It refers to an office space, part of a high-rise multi-use building, simulated as located in three different weather zones (Freiburg, Naples and Almeria). The examined solar collector is modelled as vertically integrated into the building façade, and three different orientations (East, South-East and South) were taken into account. Interesting results for the energetic, economic and occupants comfort points of view are obtained. By taking into account an initial cost of the system of about 5 k€ the primary energy savings achieved by the proposed system against the traditional buildings range between 1.9 and 8.0 MWh/y (depending on the selected weather zone and backup system). The shortest payback for all the investigated weather zones is obtained for Naples, which is equal to 6.2 years.
Keywords: Air collector; Building integrated solar thermal systems; Dynamic energy performance analysis; Experimental validation; Low-cost materials